Evidence that the large neutral amino acid L-valine decreases electrically-evoked release of 5-HT in rat hippocampus in vivo. - Gartside, SE; Cowen, P; Sharp, T (1992)
L-Valine competes with tryptophan for transport into the brain and has previously been shown to decrease brain 5-HT synthesis. In the present study, the effect of L-valine on electrically evoked hippocampal 5-HT release was determined in the anaesthetized rat using microdialysis. In control animals two electrical stimulations of the dorsal raphe nucleus 120 min apart (S1 and S2, respectively) released similar amounts of 5-HT. In contrast, in animals which received L-valine (200 mg/kg) between stimulations, S2 released a significantly smaller amount of 5-HT than did S1, although basal 5-HT release was unchanged. The data demonstrate that L-valine decreases the electrically-evoked release of 5-HT in hippocampus in vivo.